Reduction of phase noise for inductor based ultra-wide band voltage controlled oscillator - Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (IEEE., 2017)
Several techniques have been investigated in this paper to propose the reduction of phase noise due to electro-magnetic interference for inductor based ultra-wide band voltage controlled oscillator (VCO). Furthermore, figure of merit of VCO and its tuning range have been compared to exhibit the improved performance. According to article, phase noise has been stated as -151 dBc/Hz at 20 MHz offset frequency and tuning range has been implied as 69.76% of 4.3 GHz center frequency. Electro-magnetic coupling has been decreased to 44 dB by 8-shaped inductor based harmonic VCO proposed in the literature.